Enhancing the mechanical properties in the weld nugget zone of friction stir welded 2195 Al–Li alloy joint via superimposing ultrasonic vibration. (December 2022) - Tian, Chunyan; Dai, Xiang; Shi, Lei; Wu, Chuansong
Abstract: Enhancing the joint properties of Al–Li alloys is of paramount importance to reduce the weight of aircraft. Third-generation 2195 Al–Li alloy was welded by the ultrasonic vibration enhanced friction stir welding (UVeFSW). And the effect of superimposing ultrasonic vibration on grain structure, precipitates and dislocations in the weld nugget zone was studied. It reveals that superimposing ultrasonic vibration can refine the grain size, increase the dislocation density and enhance the nucleation and growth of precipitates in the weld nugget zone of friction stir welded 2195 Al–Li alloy joint. Therefore, the mechanical properties of the weld nugget zone of the UVeFSW joint are enhanced, so the fracture was shifted to the heat-affected zone. It provides a promising method to enhance the joint properties of the third-generation Al–Li alloy. Highlights: Third-generation 2195 Al–Li alloy was welded by the ultrasonic vibration enhanced friction stir welding. The mechanical properties in the WNZ of FSW joint was enhanced by ultrasonic vibration. Superimposing ultrasonic vibration in the FSW can refine the grain size and enhance the dislocation density in the WNZ. Superimposing ultrasonic vibration in the FSW can enhance the nucleation and growth of precipitates in the WNZ.